Comparison of ipsilateral and contralateral recording in brain- stem evoked response audiometry - Sunita Ahear (Journal of All India Institute of Speech and Hearing)
The present study was conducted to compare the ipsilateral and contralateral tracing of BSERA for AC logon stimuli